Effects of Music on the Quality of Life of Family Caregivers of Terminal Cancer Patients: A Randomised Controlled Trial - Valero-Cantero, Inmaculada; Casals, Cristina; Espinar-Toledo, Milagrosa; Barón-López, Francisco Javier; García-Agua-Soler, Nuria; Vázquez-Sánchez, María Ángeles (MDPI, 2023)
The aim of this study was to investigate the effects of listening to self-chosen music on the quality of life of family caregivers of cancer patients receiving palliative home care. A total of 82 family caregivers were assigned either to the intervention group (n = 41) or to the control group (n = 41) in this double-blind, multicentre, randomised controlled clinical trial. The recruitment period was between July 2020 and September 2021. The intervention group received individualised pre-recorded music in daily 30 min sessions for 7 consecutive days. The control group was given a recorded repetition of the basic therapeutic training education also in 30 min sessions for 7 consecutive days. The primary endpoint assessed was the caregivers’ quality of life (Quality of Life Family Version and European Quality of Life visual analogue scale) before and after the intervention. The secondary endpoint was their perceived satisfaction with the intervention (Client Satisfaction Questionnaire). The music intervention was successful, producing a tangible improvement in the caregivers’ quality of life (p < 0.01) and satisfaction with the care provided (p = 0.002). The intervention was not only effective but produced no adverse effects. This study encourages the use of self-chosen music as a complementary intervention in nursing care for family caregivers of palliative cancer patients.
Keywords: Música - Aspectos fisiológicos; Calidad de vida; Informal caregivers; Complementary therapy; Alternative therapy; Palliative care; Self-reported quality of life; Client satisfaction; Music medicine